Quality of life after transcatheter aortic valve implantation: Perspectives from a Canadian data base. (29th July 2021) - Lauck, S; Yu, M; Ding, L; Webb, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: We examined changes in quality of life (QOL) of patients after transcatheter aortic valve implantation (TAVI).  Methods: We conducted an observational cohort study of consecutive patients who had TAVI between 2016-2019 in British Columbia, Canada. QOL was measured at baseline, 30-day and 1-year using the Kansas City Cardiomyopathy Questionnaire (KCCQ-OS). We used linear regression modelling to examine factors associated with 30-day changes in QOL, logistic regression modelling to identify predictors of having a poor outcome, and Cox regression modelling to ascertain risk estimates of the effect of QOL on 1-year mortality.  Results: The cohort included 1, 706 patients [742 women (43.5%)]; median [interquartile range, IQR] age 83 (77, 86). Median (IQR) baseline KCCQ-OS was 45 (28.2, 67), indicating severe impairment. Patients alive at 1-year (91.3%) reported a mean improvement of 24.1 (95% CI, 22.7-25.6) points in the KCCQ-OS at 30-day, which was sustained at 1-year (25.3; 95% CI, 23.8, 26.8). Older age, lower baseline health status, lower aortic valve gradient, lower hemoglobin, atrial fibrillation and non-transfemoral access were associated with worse 30-day QOL. At 1-year, 65% of patients had a favourable outcome; additional risk factors for 1-year mortality (8.7%) were male sex, NYHA Class IV, severe pulmonary and renal disease, diabetes, and in-patient status.   Conclusions: TAVI is associated with significant early improvement in QOL which is sustained at 1 year in a "real world" registry.  The inclusion of QOL can support treatment decision and the patient-centred evaluation of TAVI